Software Application for Design of Structural Element Using Visual Basic Coding (International Journal of Engineering and Computer Science, 2017)
The increasing reliance of engineers on computer software in the performance of their tasks requires engineers, the future professional engineers, must be knowledgeable of sound engineering concepts, updated on the latest computer technology used in the industry and aware of the limitations and capabilities of the computer in solving engineering problems. “Computer Methods in Civil Engineering” to developed structural design program for design of structural element using Visual Basic. By creating my own software applications will demonstrate my creativity and integrate concepts, methods and skills in mathematics, basic engineering and specialized civil engineering subjects. This paper presents the learning objectives, requirements, methodology and outputs of my knowledge on “Computer Methods in Civil Engineering”.